2001
DOI: 10.1364/oe.8.000452
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of ultrashort light pulses in a two-level medium visualized with the finite-difference time domain technique

Abstract: The finite-difference time-domain technique is employed to examine the evolution of the amplitude, duration, waveform, and phase of ultrashort light pulses propagating in a medium of two-level atoms or molecules. The results of these numerical simulations agree reasonably well with predictions of the McCall-Hahn analysis for the evolution of the amplitude and the phase of short pulses in a two-level medium until the pulse duration becomes less than the duration of a single optical cycle. Noticeable deviations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
36
0
6

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 16 publications
2
36
0
6
Order By: Relevance
“…Moreover, the magnetic field quickly approaches zero at the boundary. This leads to favorable conditions for the application of analytical formulas based on the distribution (17). First, in our numerical simulations we observed that the maximum of the magnetic-field distribution indeed moves with time as (t − t 0 ) 1/2 .…”
Section: The Drude Equation and The Maxwell-drude Modelmentioning
confidence: 74%
See 1 more Smart Citation
“…Moreover, the magnetic field quickly approaches zero at the boundary. This leads to favorable conditions for the application of analytical formulas based on the distribution (17). First, in our numerical simulations we observed that the maximum of the magnetic-field distribution indeed moves with time as (t − t 0 ) 1/2 .…”
Section: The Drude Equation and The Maxwell-drude Modelmentioning
confidence: 74%
“…However, the notion of a pulse envelope is no longer appropriate for few-cycle pulses: as a consequence, the area theorem is no longer valid, see Refs. [16,17]. For few-cycle pulses, instead of the envelope area, it is appropriate to consider the electric-field area, which is defined as the time integral with infinite limits of the electric field itself (and not its envelope).…”
Section: Introductionmentioning
confidence: 99%
“…Эволюция площади импульса при когерентном распространении длинных импульсов в резонансных средах подчиняется теоре-ме площадей Мак-Колла и Хана [13][14][15][16]. Однако, как показывают исследования, когда длительность импуль-са сравнима с периодом колебания световой волны, возможны отклонения от теоремы площадей, и по-нятие площади импульса (1) становится не примени-мым [17][18][19][20][29][30][31][32][33][34][35][36][37][38][39]. В особенности понятие площади импульса не при-менимо в случае так называемых униполярных им-пульсов, электрическое поле в которых не меняет знак в течение длительности импульса.…”
unclassified
“…Например, импульс входной площади, определяемой формулой (1) и равной 4π, расщепляется на пару 2π-импульсов СИП, распространяющихся с раз-ной скоростью [13][14][15][16]. Это явление имеет место также в случае распространения одноциклового биполярного импульса в резонансной среде [35]. Однако в случае униполярного субциклового импульса, как упоминалось выше, понятие площади импульса (1) неприменимо, и теорема площадей нарушается [35].…”
unclassified
See 1 more Smart Citation